Changes in Reactivity In Vitro of CD4+CD25+ and CD4+CD25− T Cell Subsets in Transplant Tolerance - Hall, Bruce M.; Robinson, Catherine M.; Plain, Karren M.; Verma, Nirupama D.; Tran, Giang T.; Nomura, Masaru; Carter, Nicole; Boyd, Rochelle; Hodgkinson, Suzanne J. (Frontiers in Immunology, 2017)
Transplant tolerance induced in adult animals is mediated by alloantigen-specific CD4+CD25+T cells, yet in many models, proliferation of CD4+T cells from hosts tolerant to specific-alloantigen in vitro is not impaired. To identify changes that may diagnose tolerance, changes in the patterns of proliferation of CD4+, CD4+CD25+ and CD4+CD25-T cells from DA rats tolerant to PVG cardiac allografts and from naïve rats were examined. Proliferation of CD4+T cells from both naïve and tolerant hosts was similar to both PVG and Lewis stimulator cells. In MLC to PVG, proliferation of naïve CD4+CD25-T cells was greater than naïve CD4+T cells. In contrast, proliferation of CD4+CD25-T cells from tolerant hosts to specific-donor PVG was not greater than with CD4+T cells, whereas response to Lewis and self-DA was greater than CD4+T cells. Paradoxically, CD4+CD25+T cells from tolerant hosts did not proliferate to PVG, but did to Lewis, whereas naïve CD4+CD25+T cells proliferate to both PVG and Lewis but not to self-DA. CD4+CD25+T cells from tolerant, but not naïve hosts, expressed receptors for IFN-gamma and IL-5 and these cytokines promoted their proliferation to specific-alloantigen PVG but not to Lewis or self-DA. We identified several differences in the patterns of proliferation to specific donor alloantigen between cells from tolerant and naïve hosts. Each cell populations from tolerant and naïve hosts had similar patterns of proliferation to third-party and self. Most relevant is that CD4+CD25+T cells from tolerant hosts failed to proliferate or suppress to specific-donor in the absence of either IFN-gamma or IL-5. Our findings suggest CD4+CD25+T cells that mediate transplant tolerance depend on IFN-gamma or IL-5 from alloactivated Th1 and Th2 cells.